Serum NT-Pro-BNP versus Noninvasive Bedside Inotropic Index in Paediatric Shock: A Contest of Myocardial Performance in Response to Fluid Loading - Antonius Hocky Pudjiadi; Tuty Rahayu; Stephanie Wijaya; Fatima Safira Alatas (Critical Care Research and Practice)
Background. Mild elevation of serum amino-terminal pro-B-type natriuretic peptide (NT-pro-BNP) is associated with myocardial dysfunction. A significantly lower Smith–Madigan inotropic index (SMII) has been shown to accurately represent cardiac contractility among heart failure subjects. We aim to monitor the effect of fluid resuscitation on cardiac function among paediatric patients by measuring serum NT-pro-BNP and SMII. Methods. This is an observational study on 70 paediatric shock patients. NT-pro-BNP and noninvasive bedside haemodynamic monitoring were done by using an ultrasonic cardiac output monitor (USCOM, USCOM, Sydney, Australia). The presence of cardiac diseases was excluded. SMII was obtained from the USCOM. An increase in the stroke volume index (SVI) of ≥15% indicates fluid responders. Measurements were taken before and after fluid loading. Results. Preloading NT-pro-BNP and SMII category were significantly different between the fluid responsiveness group, p=0.001 and p=0.004, respectively. Higher median NT-pro-BNP (preloading NT-pro-BNP of 1175.00 (254.50–9965.00) ng/mL vs. 196.00 (65.00–509.00) ng/mL, p=0.002) was associated with fluid nonresponders (subjects >12 months old). Preloading NT-pro-BNP <242.5 ng/mL was associated with fluid responders (AUC: 0.768 (0.615–0.921), p=0.003), 82.1% sensitivity, and 68.7% specificity for subjects >12 years old. Delta NT-pro-BNP in fluid responders (15.00 (−16.00–950.00) ng/mL) did not differ from fluid nonresponders (505.00 (−797.00–1600.00) ng/mL), p=0.456. Postloading SMII >1.25 W·m−2 was associated with fluid responders (AUC: 0.683 (0.553–0.813), p = 0.011), 61.9% sensitivity, and 66.7% specificity, but not preloading SMII. Fluid responders had a higher mean postloading SMII compared to nonresponders (1.36 ± 0.38 vs. 1.10 ± 0.34, p=0.006). Conclusion. Higher NT-pro-BNP and lower SMII in the absence of cardiac diseases were associated with poor response to fluid loading. The SMII is affected by low preload conditions.